2016
DOI: 10.1186/s12967-016-0875-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel patient-derived xenograft mouse model for pancreatic acinar cell carcinoma demonstrates single agent activity of oxaliplatin

Abstract: BackgroundPancreatic acinar cell carcinoma (PACC) is a rare malignancy, accounting for <1 % of all pancreatic neoplasms. Very few retrospective studies are available to help guide management. We previously reported the case of a patient with metastatic PACC who achieved prolonged survival following doxorubicin treatment. Personalized treatment was based on molecular and in vitro data collected from primary cells developed from their liver metastasis. We now report the characterization of a patient derived tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…BRCA1/2 -deficient tumors are sensitive to platinum-based chemotherapies and poly (ADP-ribose) polymerase inhibitors, which may provide better clinical outcome. This has been supported by continuous response to oxaliplatin in a xenograft murine model derived from the ACC patient with somatic BRCA2 mutation 51 . In humans, complete remission or prolonged relapse-free survival has been observed in patients who have metastatic ACC with either somatic or germline BRCA2 mutation treated with cisplatinum or oxaliplatin 10,52,53 …”
Section: Discussionmentioning
confidence: 93%
“…BRCA1/2 -deficient tumors are sensitive to platinum-based chemotherapies and poly (ADP-ribose) polymerase inhibitors, which may provide better clinical outcome. This has been supported by continuous response to oxaliplatin in a xenograft murine model derived from the ACC patient with somatic BRCA2 mutation 51 . In humans, complete remission or prolonged relapse-free survival has been observed in patients who have metastatic ACC with either somatic or germline BRCA2 mutation treated with cisplatinum or oxaliplatin 10,52,53 …”
Section: Discussionmentioning
confidence: 93%
“…17 In the preclinical PACC patient–derived tumor xenograft model, oxaliplatin produced a prolonged durable growth response associated with increased apoptosis, decreased serum lipase level, and increased healthy acinar cells. 45 Yoo et al 46 reported that oxaliplatin-containing chemotherapy against PACC has improved activity compared with gemcitabine. It was indicated that chemotherapeutic agents used in treating colorectal cancer might be effective in ACC of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Panc‐4 cells, which secrete lipase in the supernatant, were not characterized in detail in vitro 25 . Although its acinar properties seemed verified in histological analysis when grown as xenografts, 56 sufficient in vitro data were not provided. Third, Faraz‐ICR cells express mesenchymal markers such as vimentin and desmin, but not epithelial markers, which are unlikely to represent ACC 27 .…”
Section: Discussionmentioning
confidence: 99%